Performance analysis of thermal arc spray aluminium coating as a sacrificial anode / Muhamad Hafiz Abd Malek - Abd Malek, Muhamad Hafiz (2015)
Thermal arc spray coating is a protective coating which useful to protect steel surface from environment condition. Thermal arc spray coating offers better protection due to its capability to withstand high temperature and better corrosion control with low operation cost. Thermal arc spray coating is applied extensively in atmospheric condition to reduce corrosion rate but very less used in seawater condition. Most duty as a corrosion protection for subsea structure is carried out by cathodic protection system; putting anode as a sacrificial to protect cathode from corrosion. This research investigates suitability of aluminium material to be as a sacrificial anode and evaluate thermal arc spray aluminium coating performance as a sacrificial anode for structure protection under seawater condition by applying different coating thickness. Efficiency of aluminium alloy 99.5% material as sacrificial anode was studied by using DNV RP B401 Standard and measured by important parameters such as potential difference, anode efficiency, consumption rate and corrosion rate. It found that the material produced good consumption rate between 2.9 kg/A.year to 3.42 kg/A.year, high anode efficiency recorded at 96%, and constant potential difference at -0.712 V. Since aluminium alloy 99.5% give a good performance, then the material was used as a coating material in thermal arc spray application. 15 samples were prepared where all samples sprayed with different coating thickness ranges from 200 pm to 700 (am and immersed in artificial seawater. Daily data were recorded such as potential difference, salinity concentration, pH and corrosion rate in 12 months experiment. After completed the experiment, laboratory tests were conducted. The surface structure and cross section were examined by scanning electron microscope and energy dispersive x-ray. The hardness was inspected using Vickers Hardness testing. Surface roughness was inspected using InfiniteFocus G4 machine. From experimental results, it shows that the coating produced low corrosion rate at range of 0.013 mm/year to 0.025 mm/year and recorded potential difference between -0.79 V until -0.886 V. It indicated that the sacrificial work well in coating form. It was supported by energy dispersive x-ray result which found calcium carbonate compound exists on the coating; increasing in coating thickness directly reduced the coatinghardness from 51.2 HV to 46.6 HV. The highest hardness was at coating thickness of 200 (jm to 300 |im. It was observed only small change or no direct correlation between surface roughness and coating thickness. Overall, it can be concluded that the coating thickness at 500 [im-600 |im provides better coating performance in terms of optimum potential difference and lesser corrosion rate.